Correlation between Suppression of Tumorigenicity-2 with Left Ventricular Geometry, Left Ventricular Ejection Fraction and Quality of Life in Systolic Heart Failure Patients - Johan Gunadi; Starry Homenta Rampengan; Janry Antonius Pangemanan; Agnes Lucia Panda; Nancy Lampus; Hasjim Hasbullah (Indonesian Biomedical Journal, 2020)
BACKGROUND: Heart failure (HF) is a clinical syndrome caused by structural or functional cardiac disorders and is the final stage of every heart disease, marked by decreased functional capacity and patients’ quality of life (QoL). Suppression of tumorigenicity-2 (ST2) is a biomarker depicting heart fibrosis and remodeling that altered left ventricular geometry, which in turn decreases left ventricular contractility, decreases functional capacity, and ultimately affects the QoL of the HF patient.